2020
DOI: 10.1101/2020.08.31.20183095
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Seroprevalence of SARS-CoV-2 antibodies in children - A prospective multicentre cohort study

Abstract: Background Studies based on molecular testing of oral/nasal swabs underestimate SARS-CoV-2 infection due to issues with test sensitivity and timing of testing. The objective of this study was to report the presence of SARS-CoV-2 antibodies, consistent with previous infection, and to report the symptomatology of infection in children. Design This multicentre observational cohort study, conducted between 16th April - 3rd July 2020 at 5 UK sites, aimed to recruit 900 children aged 2 to 15 years of age. Participa… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
20
0
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
5
3
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 27 publications
1
20
0
1
Order By: Relevance
“…• Representative samples from studies of England, France, Ireland, Italy, Netherlands, Portugal, Spain, Geneva (Switzerland), and four U.S. locations (Atlanta, Indiana, New York, and Salt Lake City). [3,13,19,[108][109][110][111][112][113][114][115][116][117] • Convenience samples from studies of Belgium, Sweden, Ontario (Canada), and eight U.S. locations (Connecticut, Louisiana, Miami, Minneapolis, Missouri, Philadelphia, San Francisco, and Seattle). [18,[118][119][120] • Comprehensive tracing programs for Australia, Iceland, Korea, Lithuania, and New Zealand.…”
Section: Resultsmentioning
confidence: 99%
“…• Representative samples from studies of England, France, Ireland, Italy, Netherlands, Portugal, Spain, Geneva (Switzerland), and four U.S. locations (Atlanta, Indiana, New York, and Salt Lake City). [3,13,19,[108][109][110][111][112][113][114][115][116][117] • Convenience samples from studies of Belgium, Sweden, Ontario (Canada), and eight U.S. locations (Connecticut, Louisiana, Miami, Minneapolis, Missouri, Philadelphia, San Francisco, and Seattle). [18,[118][119][120] • Comprehensive tracing programs for Australia, Iceland, Korea, Lithuania, and New Zealand.…”
Section: Resultsmentioning
confidence: 99%
“…• Representative samples from studies of England, Ireland, Italy, Netherlands, Portugal, Spain, Geneva (Switzerland), and four U.S. locations (Atlanta, Indiana, New York, and Salt Lake City). [3,13,19,[105][106][107][108][109][110][111][112][113] • Convenience samples from studies of Belgium, France, Sweden, Ontario (Canada), and eight U.S. locations (Connecticut, Louisiana, Miami, Minneapolis, Missouri, Philadelphia, San Francisco, and Seattle). [18,[114][115][116] • Comprehensive tracing programs for Australia, Iceland, Korea, Lithuania, and New Zealand.…”
Section: Resultsmentioning
confidence: 99%
“…4 This almost certainly represented large numbers of children attending school with mild fevers and URI symptoms, caused by a variety of common circulating winter viruses Yet these URI symptoms led to many CYP being asked to quarantine or be tested for SARS-CoV-2 before returning to school. 5 Moreover there has been some uncertainty about which symptoms indicate likely COVID-19 in children and young people (CYP), as some recent studies have suggested that other symptoms such as gastrointestinal symptoms 6 or fatigue 6 7 may be common in CYP with COVID-19.…”
Section: Introductionmentioning
confidence: 99%